The global financial crisis and public sentiment towards immigration and immigrants in the Netherlands : implications for liberal democracy and political culture - Chippendale, Emma (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: The fall of the Berlin Wall in 1989 ushered in a new era of globalisation and with it, intensified levels of global migration. The movement of people across increasingly fluid and penetrable boundaries has altered the demographic profile of European states and this cultural diversity has confronted contemporary Western liberal democracies with a unique set of challenges concerning the integration of diverse groups into society for the purpose of fostering cohesion and domestic stability. The effects of cultural diversity are not limited to demographics however, and this thesis focuses predominantly on the political and public responses that this phenomenon has evoked. The context of the Netherlands provides a particularly enlightening example of the way in which attempts to manage cultural diversity have stimulated intensive debate on immigration and integration topics, which have subsequently become firmly ensconced within public and political discourse. This ongoing debate in the Dutch context has brought to the fore wider questions pertaining to citizenship, national identity and culture. More importantly, these issues have exposed the limits of Dutch tolerance: increasingly restrictionist immigration and integration policy over the last two decades, and in the last 10 years in particular, has appeared incongruous with stereotypical perceptions of the Netherlands as an ultra-liberal and progressive paragon of multiculturalism. This thesis therefore seeks to rework this image of the Netherlands by observing possible shifts in public attitudes towards immigrants and immigration in the context of considerably less favourable material circumstances, occasioned by the current global financial crisis. Attitudes towards Muslims in Dutch society are of particular interest to this research given the particular cultural and symbolic threat that Islam is considered to pose to liberal values. Realistic Group Conflict Theory provides a useful framework for analysing inter-group competition and conflict stemming from both material and non-material perceptions of threat. Whilst particular focus is accorded to the specific macro-economic conditions of the ongoing financial crisis for observing potentially shifting sentiments, this discussion is situated within a larger national debate about immigration and integration spanning two decades. Linking public perception data to analyses of Dutch integration and immigration policy, patterns of voting behaviour and the real effects of the financial crisis on the Dutch economy, the ultimate intention of this research, then, is to assess the prospects and overall “health” of liberal democracy in the Netherlands. The country‟s experiences in attempting to deal with cultural pluralism reveal that liberal democratic norms have not simply been entrenched as “givens” and they are subject to contestation and ambiguity. It is in attempts to address difference and “otherness” in society that the shortfalls of Dutch liberal democracy have been laid bare.